Hubungan Faktor-Faktor Terhadap Ketepatwaktuan Penyusunan Anggaran Pendapatan Dan Belanja Daerah Kota Surakarta - Pratama, Rizky Akbar Dian, Dr. Zulfikar, M.Si (2015)
Compilations APBD every area in Indonesia become the form of autonomy management which was related to management of area finance pass the budget compilation. For the shake of good compilation APBD well-held, hence have to pay attention the factors able to be told to have an effect on to compilation APBD timely. This research aim to analyse the factors influence related to compilation APBD timely in Surakarta Government. This research was using quantitative method by using primery data what was obtained from questioners. This research population was entire public servant sipil was laboring in budget shares Surakarta Government. Sum up sample in this research counted 50 respondents taken by purposive sampling. Analyzer used cover data quality test, classic assumption test, multiple linear regressions analyze and hypothesis test covering F test, coefficient determinasi R2 test, and t test. The results of analysis can be conclusion that the factors influencing compilation APBD timely in Surakarta Government cover the human resource capacities, appreciation (reward), sanction (punishment), society participation, comitment from entire organizational component, leadership style. Where sixth of the independent variable have an effect on signifikan to compilation APBD timely in Surakarta Government, this matter was shown by p value was each variable < 0,05. So that hypothesis raised from H1 until H6 was truth acceptable. Keyword: human resource capacities, appreciation (reward), sanction (punishment), society participation, comitment from entire organizational component, leadership style, compilation APBD timely